Cross-talk between plant defence signalling pathways: boost or burden? - Pieterse, C.M.J.; Ton, J.; Loon, L.C. van (CAB International, 2001)
Plants are exposed to very different attackers, including microbial pathogens and herbivorous insects. To protect themselves, plants have evolved defensive strategies to counteract potential invaders. Recent advances in plant defence signalling research have revealed that plants are capable of differentially activating inducible, broad-spectrum defence mechanisms, depending on the type of invader encountered. The plant hormones salicylic acid (SA), jasmonic acid (JA) and ethylene (ET) are major players in the network of defence signalling pathways. Cross-talk between SA-, JA- and ET-dependent signalling pathways is thought to be involved in fine-tuning the defence reaction, eventually leading to the activation of an optimal mix of defence responses to resist the intruder. Genetic engineering of the biosynthetic pathways of these signalling compounds and the development of protective chemicals mimicking their mode of action provide useful tools for the development of new strategies for crop protection. However, there is evidence for antagonism between SAdependent resistance to microbial pathogens and JA-dependent resistance to herbivorous insects: once a plant is conditioned to express resistance against microbial pathogens it may become more susceptible to attack by herbivores, and vice versa. Yet, the evidence for tradeoffs between pathogen and insect resistance is contradictory. This review is focused on recent experimental evidence on the relationship between SA-, JA- and ET-dependent induced resistance to microbial pathogens and herbivorous insects. In addition, we will address the question whether manipulation of defence signalling pathways, either through genetic engineering or through application of defence signal-mimicking plant protectants, will boost the plant’s immunity to potential invaders or will be a burden in crop protection strategies.
Keywords: Biologie